2016
DOI: 10.1246/cl.160542
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition Ability of an Optically Active Poly(diphenylacetylene) as a Chiral Stationary Phase for HPLC

Abstract: An optically active poly(diphenylacetylene) with a pendant amide functional group was synthesized by a macromolecular reaction of the optically inactive poly(diphenylacetylene) bearing carboxy groups with (S)-1-phenylethylamine. The obtained polymer showed good chiral recognition ability towards diverse racemates when used as a chiral stationary phase for highperformance liquid chromatography. The chiral recognition ability was substantially influenced by the chiral conformation, probably preferred-handed heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
(23 reference statements)
2
43
1
Order By: Relevance
“…Moreover, h-poly-2S resolved racemates 8 and 9, which were barely separated on poly-2S. These results therefore indicated that the preferred-handed helical conformation induced in h-poly-2S was playing an important role in its excellent chiral recognition ability, which was consistent with the results of our previous report for h-poly-4S [36]. As expected, poly-2S and h-poly-2S both exhibited higher enantioselectivities toward nine of the racemates than our previously reported poly-4S and h-poly-4S systems, respectively, bearing the same (S)-2 unit on half of their phenyl pendants [36].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, h-poly-2S resolved racemates 8 and 9, which were barely separated on poly-2S. These results therefore indicated that the preferred-handed helical conformation induced in h-poly-2S was playing an important role in its excellent chiral recognition ability, which was consistent with the results of our previous report for h-poly-4S [36]. As expected, poly-2S and h-poly-2S both exhibited higher enantioselectivities toward nine of the racemates than our previously reported poly-4S and h-poly-4S systems, respectively, bearing the same (S)-2 unit on half of their phenyl pendants [36].…”
Section: Resultssupporting
confidence: 91%
“…These results indicated that a predominantly one-handed helical conformation was induced in the polymer backbone by thermal annealing owing to the effect of the optically active pendants (h-poly-2S). A similar thermal annealing was necessary for poly-4S to form the preferred-handed helical conformation (h-poly-4S) [27,36]. This result was attributed to steric hindrance between the neighboring pendant phenyl rings, which was large enough to prevent poly-2S and poly-4S from being transformed into their preferred-handed helical conformations after the introduction of the optically active pendants.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations